TRENDS IN TOURISM DEMAND IN THE TOP VISITED EUROPEAN COUNTRIES - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to analyze the main trends in tourism demand in the top European countries in terms of tourist arrivals, overnight stays, tourism intensity, receipts, receipts/arrival, receipts/inhabitant. The correlation coefficient and regression function were used to analyze the relationship between tourist arrivals and tourism receipts. The top visited countries in Europe registered 377.8 million international tourist arrivals in 2015, by 17.07 % more than 322.7 million in the year 2007. Their market share in the EU international tourist arrivals was 78.8 % and at the world level 31.55 %. The decreasing order of these countries based on their market share in the EU tourist arrivals is: France, Spain, Italy, Germany, United Kingdom, Austria, Greece, Poland, Netherlands, Croatia and Portugal. These countries contributed by USD 302.2 Billion to the EU receipts coming from tourism, representing 80.2 % of the EU receipts. In 2015, all these 11 countries registered 2,035 million overnight stays, representing 86.5 % of the total overnight stays in the EU. Based on this indicator, the decreasing order of these countries is: Spain, France, Italy, Germany, United Kingdom, Austria, Netherlands, Greece, Croatia, Poland and Portugal. The number of overnight stays/inhabitant, reflecting tourism intensity, varied between 16.9 in Croatia and 1.9 in Poland. While the receipts/tourist arrival varied between USD 1,323 in United Kingdom, and USD 532 in France, the receipts per overnight stay varied between Euro 88 in Germany and Euro 194 in Portugal, and the receipts/inhabitant varied between Euro 248 in Poland and Euro 1,909 in Austria. The correlation coefficient, the coefficient of determination and the regression equations attested that between the number of international tourist arrivals and tourism receipts is a positive strong correlation in case of United Kingdom and Croatia. In case of Greece and Germany it was found a moderate positive correlation, while in case of Austria, France, Italy, Netherlands, Poland, Portugal and Spain it was noticed a weak correlation. Therefore, the number of tourist arrivals reflects an increased tourism demand, but it can't entirely explain the growth of tourism receipts, which are determined by many other factors.